Activation of the transcription factor NF-kB by Campylobacter jejuni - Alsayeqh, Abdullah Fayez (2007)
Campylobacter is currently the most frequently isolated food-borne bacterial pathogen worldwide. Infections caused by C. jejuni may be self-limiting enteritis or chronic conditions such as Guillain-Barre' syndrome (GBS). Although the mechanisms by which C. jejuni causes disease are not clearly understood, the activation of the transcription factor NF-KB, which controls pro-inflammatory responses, is thought to be an important contributing mechanism for initiating the host's immune responses to C. jejuni infection. Signaling pathways leading to NF-KB by pathogens and/or their products include transmembrane Toll-like receptors (TLRs) and intracellular receptors nucleotide-binding oligomerization domain proteins (NODs). This study was carried out to: 1) investigate NF-KB activation by C. jejuni, 2) provide structural details regarding the NF-KB activating component(s) in C. jejuni boiled cell extract (BeE) and 3) investigate the role of TLRs (TLR2 and TLR4) and NODs (NODI and NOD2) in mediating NF-KB activation by C. jejuni. By means of measuring reporter gene activity, NF-KB activation and subsequent cytokine production by live or heat-killed C. jejuni, or BeE were observed in a range of tissue cultures cell lines. Structural characterisation of the NF-KB activating component in BeE indicated that the bioactive structure is an alpha-linked linear oligosaccharide composed of glucose where the activation by the oligosaccharide is suppressed upon pre-treatment of BeE with amyloglucosidase. NF- KB activation was observed to be augmented in cell lines transfected with TLR2 but not with TLR4. This activation is reduced upon transfection of cells with the dominantnegative versions (DNV) of TLR-adaptor molecules MYD88 or lRAKl. Additionally, NF-KB activation by C. jejuni was observed to be independent of NOD 1 and NOD2 in cells transfected with DNV of these receptors.